2013
DOI: 10.1302/0301-620x.95b11.31376
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of severe congenital thoracolumbar kyphosis through a single posterior approach

Abstract: A combined anterior and posterior surgical approach is generally recommended in the treatment of severe congenital kyphosis, despite the fact that the anterior vascular supply of the spine and viscera are at risk during exposure. The aim of this study was to determine whether the surgical treatment of severe congenital thoracolumbar kyphosis through a single posterior approach is feasible, safe and effective. We reviewed the records of ten patients with a mean age of 11.1 years (5.4 to 14.1) who underwent surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Furthermore, spinerelated diseases such as spondylolisthesis, scoliosis, kyphosis, or spinal stenosis, are possible indications for ISS [1]. Due to the variety of indications, patients with the need for instrumental spinal surgeries are very heterogeneous and may vary from small children to frail elderly people [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, spinerelated diseases such as spondylolisthesis, scoliosis, kyphosis, or spinal stenosis, are possible indications for ISS [1]. Due to the variety of indications, patients with the need for instrumental spinal surgeries are very heterogeneous and may vary from small children to frail elderly people [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Spiro et al [22] reported their experience of surgically treating 10 congenital thoracolumbar kyphosis patients with all-posterior three-column osteotomies. In their series, they used MEP and SSEP and noted reduction in amplitude in two cases (20%) as a result of bulging of the dura posteriorly that required further posterior decompression with subsequent normalization of data.…”
Section: Discussionmentioning
confidence: 99%
“…This creates a potential bias, because presumably the patients with better outcomes (i.e., those with symptom resolution, normal wound healing, and no concern for complications) are those who would not otherwise follow up past their initial wound check evaluation. Given the obvious limitation in follow-up and available postoperative imaging studies, which precluded direct assessment of the development of spinal instability, spinal deformity, and chronic pain, we focused on the assessment of PSM fat infiltration and muscle atrophy, 5,[8][9][10][11][12] as this has been linked to the incidence of chronic back pain and is believed to predispose to spinal instability and progressive dysfunction. 9,10,12 Postlaminectomy spinal deformity is more prevalent in the pediatric population than in adults.…”
Section: Responsementioning
confidence: 99%
“…Given the obvious limitation in follow-up and available postoperative imaging studies, which precluded direct assessment of the development of spinal instability, spinal deformity, and chronic pain, we focused on the assessment of PSM fat infiltration and muscle atrophy, 5,[8][9][10][11][12] as this has been linked to the incidence of chronic back pain and is believed to predispose to spinal instability and progressive dysfunction. 9,10,12 Postlaminectomy spinal deformity is more prevalent in the pediatric population than in adults. Risk factors associated with iatrogenic spinal deformity include the use of adjuvant radiation, multilevel exposure, and the particular level of surgery (incidence is higher for cervical > thoracic > lumbar cases); 3 hence we sought to compare equivalentlevel surgeries.…”
Section: Responsementioning
confidence: 99%